The Impact of Positive Leadership on the Well-Being of Mid-Level Leaders and the Well-Being of Employees at Korek Telecom - Mohsin, Laith Shakir; Radhi, Nagham Rasool (Journal of Ecohumanism, 2024)
Background: Studies related to positive leadership are gaining more attention from business organizations. OBJECTIVE: This study focuses on the impact of middle management’s positive leadership on the well-being of lower-level leaders and the well-being of employees. METHODS: The study used a quantitative approach through a survey, and a purposive sampling method was chosen to select (134) managers and employees, working in the middle and lower departments at Korek Telecom in the city of Erbil, Iraq. Data were obtained through a questionnaire distributed to the research sample, which was measured using a five-point Likert scale to obtain the required data. Multiple linear regression analysis using SPSS was used to interpret the data. RESULTS: The results of the data analysis indicate that positive leadership of middle management leadership has a high impact on the well-being of lower-level leaders. Furthermore, positive leadership of middle management leadership also has a high impact on the well-being of employees. The analysis indicates that an increase in the positive leadership of middle management will enhance the well-being of lower-level leaders and the well-being of employees, and lead to tangible performance. From a broader perspective. CONCLUSIONS: This research provides encouraging insights for mobile telecom companies in Iraq to enhance the work performance of leaders and employees.